PENENTUAN UMUR SIMPAN LEMANG LAHAT DALAM KEMASAN AKTIF SILIKA GEL MENGGUNAKAN METODE ASLT (ACCELERATED SHELF LIFE TEST) - Melati Pratama pratama; Arief Marna Sonjaya (BPFP Faperta UNIB, 2023)
The objective of this research was to determine the shelf life of lemang by using the parameters of water content, the characteristic of organoleptic (color, texture, aroma, taste), and microbial growth parameters. The design used in this research was a Factorial Completely Randomized Design (FCRD) with two factors, weight of silica gel (0,1,3 and 5 gs) and storage time (0,3,5 and 7 days). The method used to calculate shelf life was ASLT (Accelerated Shelf Life Test) using water content, organoleptic value, and microbial growth data (Total Plate Number). This research showed a decrease in water content, a decrease in the level of organoleptic liking (color, texture, aroma, and taste), and an increase in the number of lemang microorganisms at various treatments during storage. Based on the parameters of water content, color, texture, aroma, and taste, lemang had a maximum shelf life of 3 days. Lemang with 0 g treatment had a shelf life of 3 days only from the color preference level, while lemang with 3 g treatment had a shelf life of 3 days from color, texture, aroma, and taste preference levels. Lemang with 1 g treatment had a shelf life of 3 days from color, texture, and taste preference level. Lemang with 5 g treatment had a shelf life of 3 days from color, aroma, and taste.